PENGARUH PEMBERIAN TUMBUHAN AIR PADA AIR LIMBAH RUMAH TANGGA TERHADAP PERTUMBUHAN IKAN GURAMI (Osphronemus gouramy) SEBAGAI INFORMASI BAGI MASYARAKAT TENTANG PENCEMARAN LINGKUNGAN DAN DAUR ULANG LIMBAH - Exaputra, Hafzon (Bioedukasi Jurnal Pendidikan Biologi, 2016)
Utilization fern (Azolla pinnata) and water hyacinth (Eichhornia crassipes) in addition to preserving the environment also produces elements that are needed for the growth of living things. Household wastewater by plants Azolla pinnata and hyacinth will return sustainability, and can be used as a maintenance gourami (Osphronemus gouramy).       The purpose of this research are: (1) to determine the effect of aquatic plants in domestic wastewater to the quality of the water quality standard household waste and growth of carp (Osphronemus gouramy). (2) to find out which one is better growth of carp (Osphronemus gouramy) in household waste water between the new and old by fern (Azolla pinnata) and by plants hyacinth (Eichhornia crassipes). (3) as a source of information for the public about environmental pollution and recycling of waste water by using plants in domestic wastewater.       This type of research experiments. Samples of each treatment 20 fish carp with 4 treatments. Treatment I (wastewater new households by ferns), treatment of II (wastewater new households by plants hyacinth), Treatment III (domestic wastewater long by ferns), treatment IV (household wastewater long by water hyacinth plants). The measured parameters ie width, length and weight of carp within a certain period. Data were analyzed using Analysis of Variance (ANOVA) two lanes and qualitative analysis.       The results obtained by analysis of existing water plants on the effect of domestic wastewater on growth of carp (Osphronemus gouramy), as well as the provision of fern (Azolla pinnata) provides the most good influence on the growth of carp.Kata Kunci: Tumbuhan air, air limbah rumah tangga, pertumbuhan ikan gurami.